IMPROVING ARABIC LANGUAGE SKILLS THROUGH DIFFERENTIATE LEARNING - Zulkarnain, Yudo; Khoir, Mulyanto Abdullah (Proceeding of International Conference of Islamic Education, 2023)
Differentiated learning is an attempt to adapt the learning process in class to meet the individual learning needs of each student. The adjustments in question are related to interests, learning profiles, student readiness in order to achieve increased learning outcomes. The author finds that differentiated learning is able to help students achieve optimal learning results, because the products they will produce are according to their interests. Through differentiated learning activities, all students' learning needs are accommodated according to their interests or learning profiles. Furthermore, the authors found that there were four (4) differentiated learning components, namely: content, process, product, and learning environment. Differentiated learning processes can also provide ample space for students to demonstrate what they have learned so that differentiated learning indirectly encourages student creativity. In addition, because creativity will continue to develop, differential learning is an approach that is highly recommended to be applied in learning so as to facilitate the achievement of learning objectives.